Implementasi Nilai-Nilai Aqidah Akhlaq Dalam Meningkatkan Kepedulian Sosial - Maftuchatur Rohmah; Layli Masruroh (Universitas Ahmad Dahlan, 2019)
One of the subjects taught at school is Aqidah Akhaq. This learning is done to instill good aqidah and morality to students. But with just learning it seems lacking without any implementation of the learning. The title of this research is